Increasing the efficiency of combined control of the rocket engine thrust vector - Pryadko, N.S.; Syrotkina, N.P.; Tokareva, E.L (Технічна механіка, 2019)
This paper focuses on the drawback of the new concept of thrust vector control, which consists in the need for heavy-mass drives to rotate engine components. The paper presents and substantiates a new solution on eliminating the above drawback by transferring the function of the rotary drives to the gas-dynamic system.